Near-infrared surface sensitizing of PA12 to enable diode laser-based Powder Bed Fusion - Stratmann, Nadine; Willeke, Michael; Leupold, Simon; Schmidt, Michael; Barcikowski, Stephan; Ziefuss, Anna Rosa (Procedia CIRP, 2024)
Laser-based powder bed (PBF-LB) fusion of polymers has emerged as a versatile technique for additive manufacturing (AM), offering laynew processing freedom through promising beam-shaping techniques. This study explores a novel approach to overcome the NIR absorption limitations of the market-dominant standard material polyamide 12 (PA12) by increasing the sensitivity for effective diode laser processing through surface modification with NIR-Absorbing nanoparticles (NPs). The investigation encompasses nano sensitization strategies and theoretical analysis of energy input to the polymer, alongside comparisons with volume-modified polymer feedstocks, demonstrating that diode laser printing of surface-modified (s-mod) PA12 is possible with a macroscopic quality comparable to a commercially available volume-modified (v-mod) feedstock.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Lanthanum hexhaboride; nanocomposite; Nanoparticles; Polymer powders; Pulsed laser fragmentation in liquid; SLS